Pharmacoeconomic Analysis of Price Variability in Topical Tofacitinib and Crisaborole Across Different Brands in India: Implications for Accessibility and Regulatory Policy - Singh, Shaifali; Verma, Hemlata; T S, Amruthadevi; Nand, Stephen (Journal of Neonatal Surgery, 2025)
Background: The Indian pharmaceutical sector is characterized by notable price disparities across different brands of identical drug formulations and strengths. This variation poses substantial challenges for affordability, especially given the limited scope of medical insurance coverage in India, which escalates out-of-pocket healthcare costs. Our study aimed to evaluate the pricing disparities of topical Tofacitinib and Crisaborole and assess their potential effects on the accessibility and affordability of these treatments. Methodology: We conducted an analysis on seven Tofacitinib and seventeen Crisaborole formulations available in the Indian market. Data on pricing were collected from the 1mg online platform from January to April 2024. The analysis included calculating the cost range, mean cost, cost ratio, and percentage price variation for each drug strength. The study focused exclusively on standalone topical formulations represented by multiple brands, excluding single-manufacturer generics and fixed-dose combinations. Results: Our findings reveal that Tofacitinib 20 g strength displayed the most significant price variation at 11%, while the 15 g strength exhibited the least variation at 6%. For Crisaborole, the 30 g strength had the most substantial price fluctuation at 262%, whereas the 10 g strength had the lowest at 50%. The diversity in the number of brands per drug strength ranged from 2 to 17, indicating differing levels of market competition. Conclusion: The study underscores critical price disparities in topical Tofacitinib and Crisaborole formulations that could hinder patient adherence and economic accessibility. To mitigate these disparities, pharmacoeconomic research and regulatory interventions are imperative. These should include strategies for enhanced regulatory oversight and the implementation of transparent pricing mechanisms, thereby ensuring equitable access to vital medications without compromising their therapeutic efficacy.